Effect on direct injection naturally aspirated diesel engine characteristics fuelled by pine oil, ceiba pentandra methyl ester compared with diesel. (October 2016) - Panneerselvam, N.; Ramesh, M.; Murugesan, A.; Vijayakumar, C.; Subramaniam, D.; Kumaravel, A.
Highlights: In this research, pine oil is mixed with bio-diesel. Pine oil break thermal efficiency was increased. The bio-diesel NOx emission decreased. Abstract: This paper explores the experimental investigation of the performance, emission and combustion characteristics of bio fuels from ceiba pentandra methyl ester (CPME), ceiba pentandra methyl ester-pine oil blends (CPMEP) and pine oil and the results are compared with diesel. In ceiba pentandra seed oil the CPME yield is 92% by using transesterification process with the optimum conditions of 560 rpm, reaction time 58 min, catalyst concentration 13 g and methanol amount 500 ml. The viscosity of CPME is high when compare with diesel. So the low viscosity of pine oil is blended with CPME and it can be directly used in diesel engine without any modification. At different loads the Pine oil, CPME and CPMEP blends were used in direct injection naturally aspirated compression ignition engine. The outcomes exhibited that at full load conditions for CPME and CPMEP blends increased brake specific fuel consumption, and decreased brake thermal efficiency, CO, HC emissions. NOx emissions decreased and smoke emissions are increased on CPME and CPMEP blends, expect B25 blend compared with diesel. The combustion analysis like the heat release rate, peak cylinder pressure, cumulative heat release rate and ignition delay for CPME, CPMEP blends slightly lower and combustion duration higher than diesel and pine oil. At the Same engine operating condition, the engine fuelled with pine oil the values of brake thermal efficiency 4.79%, peak cylinder pressure, heat release rate, cumulative heat release rate and ignition delay are increased. Brake specific fuel consumption, CO, HC, and smoke were 9.46%, 16.66%, 14.89% and 8.33% decreased. However, the NOx emission is 8.29% higher than that of diesel. Experimental fuels up to B50 (50% pine oil and 50% CPME) blends have proved good potential for future energy is needed.